Content and Language Integrated Learning Practice in English for Accounting Course - Nugroho, Arif (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
The contextualization of materials in the context of teaching English for specific purposes (ESP) is a prerequisite to gain maximum input of language knowledge. The present study sheds some light on the practice of Content and Language Integrated Learning (CLIL) approach in English for accounting course. This study involved 38 Indonesian ESP students majoring in accounting of a public university in Surakarta Indonesia as the participants. Pre-experimental research design was conducted in eight meeting during the course, including the administration of vocabulary test to examine the participants’ score in pre-test and post-test. A focus group discussion (FGD) was also carried out to reveal the students’ perception about the practice of CLIL approach in English for accounting course. The results depicted that there was a significant difference on the participants’ vocabulary scores between the pre-test and the post-test. It was also portrayed that the participants positively perceived the CLIL practice in their class. The results of this study contribute to providing fruitful insights for teachers and future researchers about CLIL practice in English language teaching, specifically in the context of teaching English for specific purposes.